SOLITARY PLASMACYTOMA - Sara Grammatico (Mediterranean Journal of Hematology and Infectious Diseases, 2017)
Solitary plasmacytoma is a rare disease characterized by a localized proliferation of neoplastic monoclonal plasma cells, without evidence of systemic disease. It can be subdivided into solitary bone plasmacytoma, if the lesion originates in bone, or solitary extramedullary plasmacytoma, if the lesion involves a soft tissue. Incidence of solitary bone plasmacytoma is higher than solitary extramedullary plasmacytoma. Also prognosis is different: even if both forms respond well to treatment, overall survival and progression free survival of solitary bone plasmacytoma is poorer than solitary extramedullary plasmacytoma due to its higher rate of evolution in multiple myeloma. However, the recent advances in the diagnosis of multiple myeloma can better refine also the diagnosis of plasmacytoma. Flow cytometry studies and molecular analysis may reveal clonal plasma cells in the bone marrow; magnetic resonance imaging or 18 Fluorodeoxyglucose positron emission tomography could better define osteolytic bone lesions. A more precise exclusion of eventual occult systemic involvement can avoid cases of misdiagnosed multiple myeloma patients, that were previously considered solitary plasmacytoma and less treated, with an unavoidable poor prognosis.